EFEKTIVITAS EKSTRAK DAUN SELASIH (Ocimum Sp.) DAN DAUN WANGI (Melaleuca bracteata L.) SEBAGAI ATRAKTAN LALAT BUAH PADA TANAMAN CABAI - Shahabuddin Shahabuddin (Agroland: Jurnal Ilmu-ilmu Pertanian, 2011)
The research aimed to identify (1) the attractiveness of leaf extract of Ocimum sp. and M. bracteataon fruit flies in chili plantation and (2) species of fruit flies collected from the plantation. The studywas conducted from March to April 2009 using a Completely Randomized Block design with 3treatments of traps and 4 replications. The results showed that leaf extract of Occimum sp. and M.bracteata were effective attractants for trapping and controlling fruit flies at the chili plantation.The number of fruit flies trapped on both attractant was significantly higher compare with thattrapped on control (without attractant) but M.bractetata extract showed a higher attractiveness tofruit flies compare with Occimum sp. extract. However, the effectiveness of those attractants wasdecreased with time. The species of fruit flies recorded was Bactrocera dorsalis Hendel.Key words: Attractans, fruit flies, Occimum sp., M. bracteates.